(untitled) (Revista Innova Educación, 2022)
Due to the confinement caused by the pandemic declared in 2020, educational institutions at various levels implemented strategies to continue activities through virtual means that over time have caused emotional effects and stress in academic communities and that can cause school dropout. At the Autonomous University of the State of Hidalgo, Mexico, the need to know these affectations applied to students who are enrolled in the Bachelor of Tourism educational program is identified, through a non-probabilistic study due to the situation of the pandemic, cross-sectional, of a quantitative nature, with a convenience sample of 280 students applying the partial squares method, whose results show that the confinement caused in the case of exhaustion is considered weak; fear of getting sick from Covid-19 such as moderate school dropout; concluding that these factors can directly or indirectly influence school dropout.